Variability of the mitochondrial genome in young Yakut patients with breast cancer - D. G. Tikhonov; A. N. Egorov; M. V. Golubenko; A. Yu. Molokov; V. A. Belyavskaya; P. A. Gervas; N. A. Skryabin (Сибирский онкологический журнал, 2024)
Background. The Sakha (Yakutia) population, the indigenous population of Siberia living in Yakutia, has one of the lowest rates of breast cancer (BC) incidence worldwide. The low BC incidence among the indigenous population of Yakutia has been reported by several authors, but to date the reasons for this phenomenon have not been fully elucidated. It should be noted that the study of factors that reduce the risk of BC is important for its prevention. In several studies, no hereditary BC was found in the Yakuts, and no pathogenic variants of the BRCA1/2 genes associated with hereditary syndromes of breast and ovarian cancers were found. In this regard, we decided to shift the focus to studying the mitochondrial genome of Sakha BC patients using the sequencing method.The purpose of the study was to identify BC-associated mitochondrial genome variants in Sakha patients.Material and Methods. The study included 14 Sakha patients diagnosed with BC. The median age of the patients was 49 years. DNA isolation was performed using phenol-chloroform extraction. DNA libraries were prepared using the Nextera Flex kit (Illumina, USA).Whole-genome sequencing of the mitochondrial genome was performed on a MiSeq instrument (Illuminа, USA). in the Shared Use Centre of the Research Institute of Medical Genetics, Tomsk National Research Centre of the Russian Academy of Sciences. The results obtained in BC patients were compared with those of control subjects.Results. In Sakha women with BC, 159 mitochondrial genome variants that differed from the human mitochondrial DNA (mtDNA) reference sequence (rCRS) were identified. Likely pathogenic variants m.3736G>A of the MT-ND1 gene and m.7279T>C of the MT-CO1 gene were shown to be associated with BC. For the first time, variants predisposing to BC (m.10398A>G; m.14783T>C; m.15043G>A; m.15301G>A) were identified. A distinctive feature of the mitochondrial genome of populations with a low BC incidence is a high level of mtDNA variants with changes in the length of the polycytosine region in the D310 locus.Conclusion. For the first time, mtDNA variants with changes in the length of the polycytosine tract in the D310 locus and likely pathogenic variants m.3736G>A of the MT-ND1 gene and m.7279T>C of the MT-CO1 gene were identified in Sakha BC women. The data obtained indicate that further studies on the role of the identified mtDNA variants in the development of BC using a larger sample of Sakha patients are required.